Pathogen spreading during the COVID‐19 pandemic: Understanding a global phenomenon - Peter B. Crabb (Wiley, 2023)
Abstract This study examined news media reports published during the early months of the COVID‐19 pandemic that described people spitting, coughing, and otherwise spreading respiratory fluids to other people and objects. A search of a news archive yielded more than 800 news articles published during March, April, and May, 2020, from which N = 325 cases of intentional pathogen spreading were identified. This was during the early part of the pandemic when the world was still trying to reach an understanding of how to deal with the pandemic. Collected news articles showed that cases of intentional pathogen spreading were reported to have occurred in 14 countries on 5 continents on most days (78.3%) of the 3‐month period considered. In 43% of cases, perpetrators claimed to be infected with the SARS‐CoV‐2 virus. Frontline key workers, passersby, and retail workers were the most frequent targets. The findings suggest that more needs to be learned about intentional pathogen spreading behavior, with the goals of reducing its occurrence in future pandemics and protecting vulnerable targets.